History of Artificial Intelligence and Its Potential to Revolutionising the Interior Design Industry - Mahendarto, Trias (Journal of Artificial Intelligence in Architecture, 2025)
With its constant development and refinement, artificial intelligence (AI) has incorporated itself in many practical fields, including design. Interior design, as part of the design discipline, has also begun to incorporate AI into its industry, from the design process to the production process. Due to its constant evolution, the current studies of AI’s influence in the interior design industry are often limited to singular focus areas, creating an incomplete assessment of the correlation and impact of AI on the interior design industry. This research studies the impact of AI on the interior design industry, from the historical development of AI and its implementation in interior design in general, its integration into the design process, its application to the workflow and production process, to its current challenges and limitations in the interior design industry. The research uses a literature study, which chooses scientific writings and research that this research considered significant in the study of AI’s influence and potential in the interior design industry. This research provides insights for interior design and artificial intelligence professionals, researchers, and stakeholders. It highlights the importance of interdisciplinary collaboration to maximize the potential of artificial intelligence in the interior design industry.